2011
DOI: 10.1109/tnn.2010.2089641
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Complexity Echo State Network

Abstract: Reservoir computing (RC) refers to a new class of state-space models with a fixed state transition structure (the reservoir) and an adaptable readout form the state space. The reservoir is supposed to be sufficiently complex so as to capture a large number of features of the input stream that can be exploited by the reservoir-to-output readout mapping. The field of RC has been growing rapidly with many successful applications. However, RC has been criticized for not being principled enough. Reservoir construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
413
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 594 publications
(427 citation statements)
references
References 34 publications
10
413
1
3
Order By: Relevance
“…It has been shown in [18] that a low complexity structure (which minimizes the number of connections between the neurons) can achieve the same performances as a random interconnection matrix as initially proposed. In the ESN studied in this paper, we used a circular matrix for the connections between the neurons:…”
Section: Echo State Networkmentioning
confidence: 99%
“…It has been shown in [18] that a low complexity structure (which minimizes the number of connections between the neurons) can achieve the same performances as a random interconnection matrix as initially proposed. In the ESN studied in this paper, we used a circular matrix for the connections between the neurons:…”
Section: Echo State Networkmentioning
confidence: 99%
“…We experimented with different reservoir sizes, containing between 10 and 50 units. In many ESN applications it has been shown that the reservoir size is an important parameter [19]- [21]. As in all learning systems, there is a tradeoff to reach in that parameter.…”
Section: Methodsmentioning
confidence: 99%
“…Even though spiking neurons have more computational power than sigmoidal neurons [18], we have chosen to use the ESN for estimating PESQ scores in real-time. In the past few years there has been a growing interest in the ESN model, since it has been proven efficient and robust in many machine learning benchmark problems [4], [5], [7]- [9], [19]- [21]. The device proposed in this paper is based on this tool, in order to exploit its simplicity and its robustness.…”
Section: Description Of the Methods Proposedmentioning
confidence: 99%
“…Then, W W T = r 2 I. An example of such a system was studied in detail in [7] under the name Simple Cycle Reservoir (SCR). In SCR the couplings have the cyclic form W = r · [e 2 , e 3 , ..., e N , e 1 ] and 0 < r < 1.…”
Section: Short Term Memory Capacity and Fisher Memory Curve -Symmetric Wmentioning
confidence: 99%